Brandom and Kant on the normativity of concepts and rules - Muntaabski, Bruno Gabriel (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In the last two decades there has been a growing interest in contemporary anglo-speaking philosophy on the relation between norms and judgments as a key to understanding the nature of the mind. In this vein, Robert Brandom has elaborated an ambitious philosophical project, which he explicitly acknowledges as taking up several theses that he attributes to Kant’s philosophy. Brandom has argued that kantianism represents a normative turn regarding the nature of human concepts, one that needs to be thought of as a kind of intellectualist normativism. Additionally, he considers that the wittgensteinian reflections on rule-following constitute a strong argument against this specific type of normativism. Brandom thus establishes a critically mediated reappropriation of Kantian philosophy through a pragmatist lens. The purpose of the present paper is to study the kind of normativity attributed to Kant in this interpretation, and to develop arguments against it. The hope is to develop a better understanding of the relationship between Kantian critical philosophy and Brandomian rationalist pragmatism concerning the normative nature of concepts and rules.